HEAVY METALS IN URBAN PARK SOILS FROM ATHENS, GREECE - Papazotos, P.; Chalkiadaki, O.; Chatzistamatiou, E.A.; Georgopoulos, G.; Gkiouleka, I.; Katsikis, I.; Zygouri, E.; Kelepertzis, E.; Argyraki, A. (Bulletin of the Geological Society of Greece, 2016)
Urban geochemistry is a scientific discipline which is growing in the recent years mainly because of the environmental impact caused by urbanization. The present study aims to determine the concentrations of potentially harmful elements (PHEs) on surface soils (0-10cm) in Athens parks. Soil sampling was carried out in public park areas within the Athens urban area. Twenty surface soil (0-10cm) samples were collected and the <100μm grain size fraction was analyzed by Flame Atomic Absorption Spectroscopy for Pb, Zn, Ni, Cu, Mn andCr after a strong acid dissolution and partial extraction by 1M HCl. The organic soil matter content was determined by a combustion method. Two different inter-correlated groups of elements were identified, one including Pb, Zn, Cu showing the anthropogenic signature on urban soil and another including Cr, Ni and Mn showing geogenic origin. The mobility of the heavy metals determined in the present study follows the decreasing order: Pb> Mn >Ni≈ Cu≈ Zn> Cr. The data indicate that park areas seem to be important sinks of anthropogenic elements in urban soils.